Synthesis of core-fluorinated bis(benzoxazine)-containing monomers with 1,4-tetrafluorobenzene or 4,4′-octafluorobiphenylene dioxyphenylene central units - Kobzar, Ya. L.; Tkachenko, I. M.; Shekera, O. V.; Shevchenko, V. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
New bis(benzoxazine)-containing compounds with 1,4-tetrafluorobenzene or 4,4′-octafluorobiphenylene dioxyphenylene central units are obtained by the reductive amination of azomethine-containing bisphenols with subsequent condensation of the obtained compounds with paraformaldehyde. The structure of synthesized monomers was characterized by IR, 1H, 13C, and 19F NMR spectroscopy techniques. The synthesized compounds are of interest as monomers for the synthesis of corefluorinated polybenzoxazines.